Molecular Detection and Identification of Spotted Fever Group Rickettsiae in Ticks Collected from the West Bank, Palestinian Territories. - Suheir Ereqat; Abedelmajeed Nasereddin; Amer Al-Jawabreh; Kifaya Azmi; Shimon Harrus; Kosta Mumcuoglu; Dimtry Apanaskevich; Ziad Abdeen (Public Library of Science (PLoS), 2016)
Tick-borne rickettsioses are caused by obligate intracellular bacteria belonging to the spotted fever group (SFG) rickettsiae. Although Spotted Fever is prevalent in the Middle East, no reports for the presence of tick-borne pathogens are available or any studies on the epidemiology of this disease in the West Bank. We aimed to identify the circulating hard tick vectors and genetically characterize SFG Rickettsia species in ixodid ticks from the West Bank-Palestinian territories.A total of 1,123 ixodid ticks belonging to eight species (Haemaphysalis parva, Haemaphysalis adleri, Rhipicephalus turanicus, Rhipicephalus sanguineus, Rhipicephalus bursa, Hyalomma dromedarii, Hyalomma aegyptium and Hyalomma impeltatum) were collected from goats, sheep, camels, dogs, a wolf, a horse and a tortoise in different localities throughout the West Bank during the period of January-April, 2014. A total of 867 ticks were screened for the presence of rickettsiae by PCR targeting a partial sequence of the ompA gene followed by sequence analysis. Two additional genes, 17 kDa and 16SrRNA were also targeted for further characterization of the detected Rickettsia species. Rickettsial DNA was detected in 148 out of the 867 (17%) tested ticks. The infection rates in Rh. turanicus, Rh. sanguineus, H. adleri, H. parva, H. dromedarii, and H. impeltatum ticks were 41.7, 11.6, 16.7, 16.2, 11.8 and 20%, respectively. None of the ticks, belonging to the species Rh. bursa and H. aegyptium, were infected. Four SFG rickettsiae were identified: Rickettsia massiliae, Rickettsia africae, Candidatus Rickettsia barbariae and Candidatus Rickettsia goldwasserii.The results of this study demonstrate the geographic distribution of SFG rickettsiae and clearly indicate the presence of at least four of them in collected ticks. Palestinian clinicians should be aware of emerging tick-borne diseases in the West Bank, particularly infections due to R. massiliae and R. africae.